Trade and environment : a study of India's leather exports - Sankar, U. (New Delhi ; New York : Oxford University Press, 2007)
Contributed articles presented earlier at a seminar.
Includes bibliographical references.
Keywords: Leather industry and trade -- India -- Congresses